Analyzing the Role of Organizational Behavior in Fostering Optimal Employee Performance at the Cirebon Regency Health Office: Menganalisis Peran Perilaku Organisasi dalam Mendorong Kinerja Optimal Pegawai Dinas Kesehatan Kabupaten Cirebon - Sadli, Mohamad; Nurjannah, Ana (Medpro, 2025)
Modern organizational dynamics demand a profound understanding of organizational behavior (OB) as a primary key to enhancing employee performance. In the context of public services, especially in the vital healthcare sector, optimal employee performance is essential to ensure service quality and the achievement of strategic targets. This study analyzes the role of organizational behavior in fostering optimal employee performance at the Cirebon Regency Health Office. It aims to identify the extent to which interactions and work culture within the office environment influence employee effectiveness and productivity, as well as to pinpoint the OB variables that contribute most to performance. The research employed a quantitative descriptive method with a cross-sectional design, collecting data simultaneously from 45 respondents, representing a 25% sample of the total population of 180 employees at the Cirebon Regency Health Office. A questionnaire was used for primary data collection, complemented by secondary data, and subsequently analyzed using the Chi-Square test with a 95% significance level (α=0.05). Data collection was conducted from January 2-10, 2025, at the Cirebon Regency Health Office. The findings reveal a p-value of 0.005 (α<0.05), indicating a significant relationship between organizational behavior and employee performance at the Cirebon Regency Health Office. This result underscores the importance of positive organizational behavior in creating a supportive work environment conducive to achieving the best possible performance. This research contributes by providing strategic recommendations for the Cirebon Regency Health Office, particularly concerning the implementation of technology systems to support real-time performance reporting and the strengthening of leadership roles as drivers of employee performance. These insights are expected to serve as practical guidelines for optimizing human resource management in the public healthcare sector.